Similarities and differences of the HR practices foreign owned subsidiaries in post-soviet region with comparison of Central and Eastern Europe countries - Poór, József; Latukha, Marina O.; Engle, Allen D.; Abdyrakhmanova, Kaiyrkul (Anali Ekonomskog fakulteta u Subotici, 2023)
Purpose of this study is to determine interrelations between HRM characteristics at local subsidiaries in six focal countries in the light of different organizational variables year of establishment, sector of MNC, mode of entry and origin of MNC in selected Post-Soviet counties in comparison to Central and Eastern Europe countries. We profile the HRM practices of almost 234 foreign owned subsidiaries located in Kyrgyzstan, Kazakhstan, Hungary, Russia, Slovakia and Poland. Using descriptive statistics, we present the general characteristics of the sample and we then use bivariate statistical analysis to test our hypotheses relating to the impact of different factors on the HR practice mix implemented in the MNC subsidiaries covered in our survey. The results support a contention that multinational companies following different HR management practices/approaches due to institutional histories. For example, in Post-Soviet Countries HR department is more centralized decision-making with tight control and the number of expatriates are lower when compared to the practices of firms in the CEE region.